2010
DOI: 10.1590/s0100-06832010000600018
|View full text |Cite
|
Sign up to set email alerts
|

Atividade de urease no solo com feijoeiro influenciada pela cobertura vegetal e sistemas de plantio

Abstract: Kliemann (5) RESUMOA urease é a enzima que catalisa a hidrólise da ureia em dióxido de carbono e amônia. A distribuição da urease e os fatores que a influenciam têm importância relevante em vista do uso da ureia na agricultura. Nesse sentido, este estudo teve como objetivo definir a época adequada de coleta de solo, após adubação nitrogenada no feijoeiro comum, para medir a atividade de urease e seu perfil, considerando os efeitos residuais de diferentes plantas de cobertura e de sistema de preparo do solo. O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 8 publications
1
7
0
6
Order By: Relevance
“…The enzyme URE is responsible for catalyzing the hydrolysis of urea to ammonia. Therefore, URE activity indicates the soil potential for transforming organic nitrogen into mineral nitrogen (Lanna et al 2010). Thus, the reduction in URE activity results in the reduction of mineral nitrogen availability in the soil, as evidenced by the reduction of N-NH 4 found in this study and also observed by others (Wang et al 2010;Zhang et al 2016).…”
Section: Discussionsupporting
confidence: 85%
“…The enzyme URE is responsible for catalyzing the hydrolysis of urea to ammonia. Therefore, URE activity indicates the soil potential for transforming organic nitrogen into mineral nitrogen (Lanna et al 2010). Thus, the reduction in URE activity results in the reduction of mineral nitrogen availability in the soil, as evidenced by the reduction of N-NH 4 found in this study and also observed by others (Wang et al 2010;Zhang et al 2016).…”
Section: Discussionsupporting
confidence: 85%
“…Urease is an extracellular enzyme produced by soil microorganisms and is responsible for the hydrolysis of urea to ammonium, bicarbonate, and hydroxyls. This ammonium can be absorbed by plants, which generally has a preference for this form at the beginning of their development (Lanna et al, 2010). Most of the Bacilus collection of this study was able to produce urease.…”
Section: Bacillus Sp Isolates Plant Growth-promoting Mechanisms In Vmentioning
confidence: 82%
“…Therefore, if there is no organic matter with quality, even with the low availability of P for the plants, the enzyme will not be activated because there will be no energy source to carry out its activities. Another factor that explains these results is that usually, areas with legume present large amounts of organic carbon, as well as organic phosphorus contained in the soil microbial biomass and low availability of inorganic phosphorus (LANNA et al, 2010).…”
Section: Resultsmentioning
confidence: 99%